THE ROLE OF MODERN OFFICE ADMINISTRATION IN IMPROVING OPERATIONAL EFFICIENCY AND QUALITY OF ORGANIZATIONAL SERVICES IN THE DIGITAL ERA - Maya Novrita Dama; Risca Marsanti Halid; Neva Lionitha Ibrahim (Universitas Negeri Gorontalo, 2025)
This study aims to analyze the role of modern office administration in improving operational efficiency and organizational service quality using a Systematic Literature Review (SLR) approach. This study fills a research gap by integrating five dimensions of modern administration into a single integrated conceptual framework. The review focuses on five main aspects: standardization of administrative procedures, digitalization and e-office implementation, electronic records management, human resource competencies, and their impact on organizational performance. The literature selection process covered publications from 2015 to 2025 across several scientific databases, resulting in 18 eligible articles out of 120 initially identified studies. The findings indicate that procedural standardization serves as the foundation for ensuring consistency and accountability, while digital systems such as e-office, ERMS, and EDMS enhance workflow speed and document accuracy. Electronic records management facilitates faster information retrieval and supports quality management systems. Furthermore, human resource competency is a key determinant of successful modern administrative implementation in improving operational efficiency and service quality.